Interlaboratory comparison of a multiplex immunoassay that measures human serum IgG antibodies against six-group B streptococcus polysaccharides - Kirsty Le Doare; Michelle A. Gaylord; Annaliesa S. Anderson; Nick Andrews; Carol J. Baker; Shanna Bolcen; Arif Felek; Peter C. Giardina; Christopher D. Grube; Tom Hall; Bassam Hallis; Alane Izu; et al. (Human Vaccines & Immunotherapeutics)
Measurement of IgG antibodies against group B streptococcus (GBS) capsular polysaccharide (CPS) by use of a standardized and internationally accepted multiplex immunoassay is important for the evaluation of candidate maternal GBS vaccines in order to compare results across studies. A standardized assay is also required if serocorrelates of protection against invasive GBS disease are to be established in infant sera for the six predominant GBS serotypes since it would permit the comparison of results across the six serotypes. We undertook an interlaboratory study across five laboratories that used standardized assay reagents and protocols with a panel of 44 human sera to measure IgG antibodies against GBS CPS serotypes Ia, Ib, II, III, IV, and V. The within-laboratory intermediate precision, which included factors like the lot of coated beads, laboratory analyst, and day, was generally below 20% relative standard deviation (RSD) for all six serotypes, across all five laboratories. The cross-laboratory reproducibility was < 25% RSD for all six serotypes, which demonstrated the consistency of results across the different laboratories. Additionally, anti-CPS IgG concentrations for the 44-member human serum panel were established. The results of this study showed assay robustness and that the resultant anti-CPS IgG concentrations were reproducible across laboratories for the six GBS CPS serotypes when the standardized assay was used.